Видовой состав и численность раковинных корненожек — Testacea (Rhizopoda) — Днепра на участке от Жлобина до Канева - Гурвич, В.В. (Вестник зоологии, 1971)
In the above-mentioned region of the Dnieper and in the reservoirs of its supplementary system 46 species of Testacea were found, 30 of them are new for this region.
Testacea are presented by holarctic species (63%), cosmopolites (22%) and by
geographically widely distributed species.
Composition and quantity of Testacea are conditioned by the type of the soil; a strong
current limits their developments. The sand soil of the Dnieper bed and its branches is
poor in Testacea. In the mud of the flood plain lakes Testacea reach their greatest development (on the average 3.3 million specemens/m2).
By the species composition, occurence and quantitative development of Testacea one
may judge about the character of biotope.